Identifying and addressing students' questions on climate change. Issue 5 (20th October 2018) - Tolppanen, Sakari; Aksela, Maija
ABSTRACT: This study uses qualitative content analysis to examine 355 open-ended questions, presented by 16–19 –year-old international students, to find out what students want to learn about climate change. The study finds that students have a high level of consideration toward scientific, societal, and ethical aspects of climate change and that students' questions are multidisciplinary and complex in nature. Most important, the findings show that students ask questions on the same themes that researchers say should be addressed in multidisciplinary climate change education. Based on the findings, this article suggests that climate change education could be developed by adopting guided inquiry.